Elicited Asynchronies in Recorded Performances of Chopin’s Mazurkas - Ohriner, Mitchell (Empirical Musicology Review, 2014)
Studies of duration in music performance since the 1980s have focused on the role of duration in the communication of musical structure, namely grouping and metric structure. This article posits a broader view of duration in performance, namely that performers choose durations to facilitate or inhibit listener-performer synchronicity. Listeners who maintain synchronicity are continually rewarded for making accurate predictions of when events will happen, and thus the loss of synchronicity might hazard feelings of frustration or isolation. Performers, by choosing durations that are difficult to predict, can therefore enlist these feelings in dynamic narratives of synchronicity that augment trajectories in the score. The article explores two such narratives, found in seventeen participants’ attempts to synchronize to two idiosyncratic renditions of passages of Chopin’s mazurkas. By ascribing significance not only to the choices of performers and composers but also to how individual listeners attend to those choices, the article aims to widen the circle of agencies ascribed with the ability to affect the meaning of musical works.